The Effect of Probiotic Supplementation in Cholestasis Liver Disease: A Systematic Review of Animal Studies - Azizah, Nur; Oswari, Hanifah; Sjatha, Fithriyah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Gut microbiome is essential in maintaining metabolism, gut barrier homeostasis, inflammation, and hematopoiesis. Several factors affect gut microbiome composition, including genetics, lifestyle, external factors, and disease. Cholestasis liver disease promotes gut dysbiosis via abnormal bile production or flow to the intestine and disrupts the gut microbiome. This condition leads to intestinal leakage, which enables bacterial and endotoxin translocation to the liver through the portal vein. Bacterial translocation promotes inflammatory responses, which worsen liver damage in cholestasis. Moreover, probiotic supplementation in other diseases has been shown to preserve gut microbiome composition. While such studies have documented probiotics' beneficial effects, no adequate clinical trials support probiotics' potency as a cholestasis treatment. Hence, this systematic review aims to provide an in-depth analysis of probiotic supplementation as a therapy for cholestasis liver disease in animal models. The search strategies were conducted based on PRISMA methodologies based on various academic literature. The selected studies have shown improvements in bile acid metabolism, microbiota-gut-liver axis, gut epithelium integrity, liver damage and inflammation response, and liver fibrosis progression, which need to be confirmed in human clinical trials.